2022
DOI: 10.3390/microorganisms10112284
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides Difficile Infection before and during Coronavirus Disease 2019 Pandemic—Similarities and Differences

Abstract: The aim of this study was to investigate the differences of Clostridioides difficile infection (CDI) during the COVID-19 pandemic compared to the pre-COVID-19 era. CDI patients treated at the Clinic for Infectious Diseases, Clinical Center of Vojvodina, Serbia during 2017–2019 (n = 304) were compared with COVID-19/CDI patients treated in period September 2021–September 2022 (n = 387). Groups were compared by age, gender, comorbidities, previous medications, laboratory findings, and outcome within 30 days. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
1
3
1
Order By: Relevance
“…Malignancy was found to be more frequent in patients without COVID-19 which was also shown in Spain [ 25 ]. In contrast to our findings, a study conducted also in our county showed that chronic renal failure, malignancy, and chronic obstructive lung disease are more frequent in HA-CDI–COVID-19 patients than in HA-CDI patients without COVID-19 [ 32 ]. A possible explanation for these differences is that this study was conducted in two separate hospitals.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Malignancy was found to be more frequent in patients without COVID-19 which was also shown in Spain [ 25 ]. In contrast to our findings, a study conducted also in our county showed that chronic renal failure, malignancy, and chronic obstructive lung disease are more frequent in HA-CDI–COVID-19 patients than in HA-CDI patients without COVID-19 [ 32 ]. A possible explanation for these differences is that this study was conducted in two separate hospitals.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, steroid use was an independent risk factor for HA-CDI in COVID-19 patients. Similar results have been shown in a study conducted in other COVID and non-COVID hospitals in our country [ 32 ]. These drugs were part of many versions of protocols for the treatment of COVID-19 patients due to their anti-inflammatory role.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous other studies have shown that due to frequent hospitalisations and a greater number of comorbidities, people older than 65 years of age have a higher risk of developing infections caused by C difficile. 17,18 The basic mechanisms as to why CDI oc-curs more often and presents a more severe clinical manifestation in the elderly population, have not been sufficiently clarified. It is believed that several associated factors, such as comorbidities, polypharmacy and frequent hospitalisations may contribute to the observed outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, high CRP values in patients with HA -CDI may be a repercussion of the presence of more serious concomitant infections of other aetiology, which puts these patients at additional risk of a poor outcome of the disease. 17…”
Section: Discussionmentioning
confidence: 99%
“…It is logical to suppose that hospitalised patients have disrupted gut microbiota and this will increase the number of CDIs, but on the contrary, a strong decrease in C. difficile incidence was observed, likely due to improvements in hand hygiene, use of personal protective equipment, and environmental cleaning in the healthcare settings [124]. However, the COVID pandemic has had a big influence; a recent study showed that COVID-19 changed the CDI patterns with a significantly greater percentage of a lethal outcome, 29.5% vs 6.6% [125]. Another study from Canada for 2020/2021 reported an increased frequency of CDIs [126].…”
Section: Treatmentmentioning
confidence: 99%